Dampak dan Hambatan yang Terkait dengan Transisi Karier di Kalangan Mahasiswa dengan Gangguan Belajar Khusus - Chiedu Eseadi (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Muhammadiyah kendari, 2024)
Students with Specific Learning Disabilities (SLD) may lose access to familiar and essential resources for career transition after graduation, compelling them to navigate social and governmental institutions independently. This study investigated the impacts and barriers associated with career transition among students with SLD. The research employed a narrative literature review technique to search for and review relevant literature. Utilizing a narrative review approach enabled the researcher to identify comparable and diverse viewpoints and patterns within the literature, generating meaningful insights into the research topic. Challenges identified in this research include difficulties with modifications or accommodations, attitudinal barriers, failure to advocate for oneself, failure to disclose one's disability to employers or schools, inadequate career preparation and planning, discrimination, and social isolation. The study emphasizes that transition challenges persist based on the reviewed literature on barriers to career transition for students with SLD. It advises career counselors and employers to adopt a more inclusive approach in counseling and workforce accommodations by accurately identifying the additional needs of students with SLD. Sharing best practices and experiences can facilitate the dissemination of knowledge, materials, and resources for working with students with SLD.